A resilient and lightweight bacterial cellulose-derived C/rGO aerogel-based electromagnetic wave absorber integrated with multiple functions. Issue 9 (3rd February 2021) - Bai, Tiantian; Guo, Yan; Wang, Dedong; Liu, Hu; Song, Gang; Wang, Yaming; Guo, Zhanhu; Liu, Chuntai; Shen, Changyu
Abstract : A resilient and lightweight bacterial cellulose-derived C/rGO aerogel-based electromagnetic wave absorber integrated with multiple functions such as piezoresistive sensing, infrared stealth, thermal insulation, and Joule heating. Abstract : Considering the complex actual environments and fields, the effective integration of multiple functions into one material is greatly and urgently required but still faces enormous challenges. Herein, an aerogel-based electromagnetic wave (EMW) absorber with the functions of piezoresistive sensing, infrared stealth, thermal insulation, and Joule heating was developed. Biomass bacterial cellulose (BC) and GO work as the carbon resource and reinforcing filler, respectively, obtaining a resilient (80% compression strain) and lightweight (7.81 mg cm −3 ) BC-derived C/thermal reduced GO (rGO) aerogel with the unidirectional cellular structure via the unidirectional freeze-drying and pyrolysis techniques. Remarkably, the prepared aerogel displayed the typical rGO loading and compression strain-dependent EMW absorption performance, and a significant improvement in the EMW absorption capacity with a minimum reflection loss (RLmin ) of −46.11 dB and maximum effective absorption bandwidth (EABmax ) of 9.12 GHz at the thickness of 2.70 mm was achieved for C/rGO-10 (10 wt% rGO loading) when a 70% compression strain was applied compared to that in the natural state. Moreover, the aerogel also presented other attractive features, including stable, durable, and fast responsive piezoresistive sensing performances, effective thermal infrared stealth, and thermal insulating properties, and exceptional adjustable Joule heating performance. This study paves the way for developing high-performance EMW absorption materials with multiple functions to meet various applications.